Criminal Liability of Notaries and State Registrars for Unlawful Actions in the Field of State Registration - Bayda, Anton; Usova, Sofiia (Problems of legality, 2026)
The article is devoted to the problems of criminal-law qualification of unauthorized actions involving information in state registers, liability for which is provided in Article 362 of the Criminal Code, examined through the lens of judicial practice reflected in the decisions of the Unified State Register of Court Decisions. The conducted analysis reveals inconsistencies in the interpretation of the subject, object, subjective and objective elements of the offense, caused by the excessive universality of the provision, which combines combating cybercrime with the regulation of official misconduct. The study, while maintaining a purely academic character, is not aimed at criticizing the legality of court decisions or the competence of judges, but focuses on the doctrinal analysis of the norm in the context of its practical application. In our view, this makes it possible to assess the effectiveness of judicial oversight, reveal the shortcomings of current regulation, and substantiate proposals for its improvement – in particular, separating offenses against automated systems from abuse of authority, strengthening disciplinary liability, and introducing technical mechanisms of prevention. The issues considered emphasize the importance of further analyzing the effectiveness of Article 362 of the Criminal Code in its current version, its role in maintaining the rule of law, and ensuring the protection of the rights of professional actors from unjustified criminal prosecution.